The influence of context and urban structure on the walkability of Bukit Bintang commercial district, Kuala Lumpur - Ujang, Norsidah; Salim, Atirah; Maulan, Suhardi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
According to Wall and Waterman (2009), the walkability of an urban district is influenced by the contextual integration between the district and the surrounding areas as well as the structure of the urban fabric. This paper discusses the context and the urban structure of Bukit Bintang Commercial District in light of the walkability criteria. Using the criteria adapted from various scholars, this study measures the walkability of the district and identifies the influencing factors through field observations. The findings indicate that the success of Bukit Bintang district as a walkable urban place is supported by the connectivity of the area to the adjacent urban nodes of Pudu and Kuala Lumpur City Centre (KLCC). The structure of the urban fabric (i.e. streets, open spaces and buildings) is legible, which provides ease of movement. However, the permeability is low in the newer parts of the area due to the presence of longer urban blocks and larger footprint shaped by the modern shopping complexes built in the 1980’s. The findings denote the need for enhanced legibility of smaller urban spaces and improved permeability of larger urban blocks. This will increase the walkability of Bukit Bintang Commercial District for the pedestrian comfort of walking